Checklist of aphyllophoroid fungi (Agaricomycetes, Basidiomycota) in boreal forests of the Solovetsky Archipelago (Arkhangelsk Region, European Russia) - Ezhov, Oleg; Zmitrovich, Ivan; Ruokolainen, Anna (Check List, 2017)
Herein we present a checklist of aphyllophoroid fungi of the Solovetsky Archipelago, located in the White Sea (Arkhangesk Region, European Russia). The annotated list contains 275 species belonging to 139 genera of aphyllophoroid basidiomycetes (Agaricomycetes, Basidiomycota). Eight species ( Athelia bombacina, Ceraceomyces tessulatus, Clavariadelphus truncatus, Clavaria zollingeri, Clavulinopsis luteoalba, Hyphoderma obtusiforme, Phanerochaete jose-ferreirae , and Ramaria obtusissima ) are recorded from the Arkhangelsk Region for the first time, and 23 species were recorded for the first time from the Solovetsky Archipelago. Most records are documented by herbarium specimens.